2014
DOI: 10.1264/jsme2.me14026
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Ferrihydrite on a Thermophilic Methanogenic Community

Abstract: The addition of ferrihydrite to methanogenic microbial communities obtained from a thermophilic anaerobic digester suppressed methanogenesis in a dose-dependent manner. The amount of reducing equivalents consumed by the reduction of iron was significantly smaller than that expected from the decrease in the production of CH4, which suggested that competition between iron-reducing microorganisms and methanogens was not the most significant cause for the suppression of methanogenesis. Microbial community analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
1
16
1
1
Order By: Relevance
“…The amounts of reducing equivalents consumed by Fe(III) reduction were 37.5% of that expected from the observed decrease in CH 4 production in the ferrihydrite‐supplemented cultures, indicating that ferrihydrite‐dependent inhibition of methanogenesis was not completely due to the direct competition between Fe(III)‐reducing bacteria and methanogens for acetate. The diversion of electron flow from methanogenesis to ferrihydrite reduction by methanogens might contribute to the direct inhibition of methanogenesis by ferrrihydrite, which has been demonstrated in microbial communities [ Yamada et al ., ] and pure culture of methanogens [ Bond and Lovley , ; van Bodegom et al ., ; Liu et al ., ; Zhang et al ., ; Yamada et al ., ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amounts of reducing equivalents consumed by Fe(III) reduction were 37.5% of that expected from the observed decrease in CH 4 production in the ferrihydrite‐supplemented cultures, indicating that ferrihydrite‐dependent inhibition of methanogenesis was not completely due to the direct competition between Fe(III)‐reducing bacteria and methanogens for acetate. The diversion of electron flow from methanogenesis to ferrihydrite reduction by methanogens might contribute to the direct inhibition of methanogenesis by ferrrihydrite, which has been demonstrated in microbial communities [ Yamada et al ., ] and pure culture of methanogens [ Bond and Lovley , ; van Bodegom et al ., ; Liu et al ., ; Zhang et al ., ; Yamada et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…The main inhibitory mechanisms was proposed as Fe(III)‐reducing microorganisms reduce the levels of primary electron donors (acetate or hydrogen) available for methane production [ Achtnich et al ., ; Jäckel and Schnell , ; Qu et al ., ] and thus increase the contribution of Fe(III) reduction to anaerobic degradation of organic matter at the expense of methanogenesis. Furthermore, the increase in redox potential of the environments by the presence of Fe(III) oxides [ Fetzer and Conrad , ; Hirano et al ., ] and the diversion of electron flow from CO 2 reduction (methanogenesis) to Fe(III) reduction by methanogens capable of Fe(III) reduction [ Bond and Lovley , ; van Bodegom et al ., ; Liu et al ., ; Zhang et al ., ; Yamada et al ., , ] have been postulated as the direct inhibition of methanogenesis by Fe(III) oxides. Thus, ferric iron fertilization of rice paddies has been suggested as a potential option for mitigating methane emissions [ Jäckel et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that washed cell suspension of certain hyperthermophilic methanogens has the ability to reduce soluble Fe(III) citrate (Vargas et al, 1998), while their ability to reduce insoluble Fe(III) minerals and the inhibitory effects of Fe(III) on their methanogenesis have not been investigated. Our group has recently reported the inhibitory effects of ferrihydrite on microbial communities obtained from a thermophilic anaerobic digester (Yamada et al, 2014). Additionally, Zhang et al (2013) has recently found the reduction of structural Fe(III) in smectite minerals by Methanothermobacter thermautotrophicus (hereafter Mtb.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a unique Bacteroidetes organism ( Proteiniphilum acetatigenes strain TB107) remarkably promotes syntrophic propionate degradation by Syntrophobacter and Methanobacterium (Chen and Dong, ). Extracellular electron transfer (EET) (or electric syntrophy) mediated by flagella/pili/cytochrome and conductive materials can be possible facilitative mechanism for methanogenesis in anaerobic bioreactors (Shimoyama et al ., ; Kato and Watanabe, ; Kato et al ., , ; Yamada et al ., ; Kato, ). The specific syntrophic associations we identified in full‐scale UASBs degrading industrial wastewater indicate the importance of characterizing microbial communities in commercially operated full‐scale wastewater treatment processes.…”
Section: Resultsmentioning
confidence: 98%